Understanding and treating trauma and violence-related pathologies in South African townships : emergence and modifiability of epigenetic and neural memories of traumatic stressors and appetitive offending - Xulu, Khethelo Richman (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.